2022
DOI: 10.1088/1757-899x/1272/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Processing and tribological behaviour of carbon fiber reinforced polylactic acid composites

Abstract: Thermoplastic composites are acquiring more importance in various tribological applications due to their self-lubricity, low melting, and ease of fabrication. In this research article, processing via fused deposition modelling and dry sliding wear behaviour of neat and short carbon fiber reinforced polylactic acid composites have been investigated. A series of wear tests using a pin-on-disc wear apparatus was carried out by varying tribo-parameters namely applied load (10, 20, and 30 N), sliding velocity (0.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Bustillos et al [24] studied the influence of graphene on PLA and showed that PLA-graphene composites presented a significant improvement in creep and wear resistance. Suresha et al [25] have demonstrated that adding 20 wt.% short carbon fibers to PLA resulted in composites with improved wear resistance (70% decrease in specific wear rate). In a recent study on PLA-based biocomposites reinforced with SCF, GNP, and SCF + GNP [26] produced by casting, we have shown that the joint addition of these two fillers (volume ratio between the PLA and the fillers of 1:0.02) had a beneficial effect on the hardness and specific wear rate of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…Bustillos et al [24] studied the influence of graphene on PLA and showed that PLA-graphene composites presented a significant improvement in creep and wear resistance. Suresha et al [25] have demonstrated that adding 20 wt.% short carbon fibers to PLA resulted in composites with improved wear resistance (70% decrease in specific wear rate). In a recent study on PLA-based biocomposites reinforced with SCF, GNP, and SCF + GNP [26] produced by casting, we have shown that the joint addition of these two fillers (volume ratio between the PLA and the fillers of 1:0.02) had a beneficial effect on the hardness and specific wear rate of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…The hafnium carbide powder with particle size ranging from 400-500 Nm was utilized as an additive for purchased from Intelligent materials, Punjab, India. The substrate was manufactured using a Flash forge-adventure 3 model 3D printer, employing optimum printing parameters including a printing temperature of 210 °C, bed temperature of 50 °C, 100% infill density, and a printing angle of 45° [3,37]. The optimal parameter for extending the lifespan of PLA-CF composites has been demonstrated to be vertical print orientation [38].…”
Section: Methodsmentioning
confidence: 99%
“…A pin on disc wear testing equipment with a heating chamber was employed to investigate the impact of ceramic particle coating on the wear resistance of an FDM produced part. The coated specimen was affixed to the pin using an adhesive, and the process of testing its resistance to wear was conducted in accordance with the ASTM standard ASTM G99 [3,11,12,45]. The test apparatus comprises an EN31 alloy steel disc, a steel pin, and a mass loading apparatus.…”
Section: Experimentationmentioning
confidence: 99%
See 1 more Smart Citation